A COMPARATIVE ANALYSIS OF AGROWASTES MODIFIED FIBER AND LIGNIN AND THEIR HYDROTHERMALLY CARBONIZED PRODUCTS (FUDMA JOURNAL OF SCIENCES, 2022)
This study investigated the use of gravimetric method of analysis to determine the Acid Detergent Fiber (ADF) and Acid Detergent Lignin (ADL) of some Agro wastes and their hydrothermally carbonized products with a view of evaluating the energy production potential. The results showed that most of the carbonized products had more ADF values as compared to their uncarbonized precursors except for cassava peels and plantain peduncle, which have values of 39.20% as against 21.65% and 41.19% and 28.22% respectively. The ADL values were all lower than those of ADF. The percentage difference for the pairs of the crop wastes and their hydrothermally carbonized products gave the highest of ADF of 54.91% for maize comb and -44.77% for cassava peels. For the ADL, the range of percentage difference is between 60.20% for rice husk and -62.23% for beans husk.  With the high ADF values for the agro - wastes and their hydrothermally carbonized products, these materials could be exploited for various energy generation.
Keywords: agro wastes; hydrothermal carbonization, Acid Detergent Fiber; Acid Detergent Lignin